Tropical cyclone response to ambitious decarbonization scenarios - Mincheol Moon; Seung-Ki Min; Jung-Eun Chu; Soon-Il An; Seok-Woo Son; Hamish Ramsay; Zhuo Wang (npj Climate and Atmospheric Science)
Abstract Numerous studies have explored global warming impact on tropical cyclones (TCs), but post-global warming TC activity remains poorly understood. This study analyzed 400-year evolution of TC characteristics in CO2 emission-driven ensemble experiments performed with the CESM2 model under net-zero (ZeroE) and negative CO2 emission (NegE) scenarios. Findings reveal a hemispheric asymmetry in TC track changes, with the Northern Hemisphere seeing a decrease and the Southern Hemisphere an increase. Under the ZeroE scenario, asymmetry persists for 300 years, while the NegE scenario mitigates it within 200 years. This asymmetry is influenced by changes in mid-level humidity, vertical wind shear, and sea surface temperature gradients. Unlike the TC frequency, maximum wind speeds and rainfall associated with landfalling TCs are enhanced globally in the ZeroE scenario, while alleviated in the NegE scenario. These results indicate that a carbon-neutral strategy is not sufficient and that more ambitious negative emission efforts are needed to mitigate TC impacts.